Effect of apigenin on tryptophan metabolic key enzymes expression in lipopolysaccharide-induced microglial cells and its mechanism. Issue 1 (January 2023) - Kurniati, Dian; Hirai, Shizuka; Egashira, Yukari
Abstract: [Aims ] Flavonoid apigenin (API) has a wide range of biological functions, particularly anti-inflammation. Indoleamine 2, 3-dioxygenase (IDO) and 2-Amino-3-carboxymuconate-6-semialdehyde decarboxylase (ACMSD) are important tryptophan metabolic enzymes that play pivotal roles in the production of toxic metabolite quinolinic acid. However, the relationship between inflammation and ACMSD remains unclear. The present study investigated the relationship between inflammation and tryptophan metabolic key enzymes. Similarly, the anti-inflammatory effect of API on important tryptophan metabolic enzymes was examined in lipopolysaccharide (LPS)-treated microglial cells. [Main methods ] MG6 cells were exposed to LPS with or without API treatment for 24–48 h. IDO and ACMSD mRNA expression and production of inflammatory mediators were analyzed. Activation of inflammatory signaling pathways, such as mitogen-activated protein kinase (MAPK) and nuclear factor-κB (NF-κB), was also examined to study the mechanism of API in the inflammatory state. [Key findings ] LPS suppressed ACMSD expression and enhanced IDO expression. However, API elevated ACMSD mRNA expression and suppressed IDO mRNA expression in LPS-treated MG6 cells. Furthermore, API suppressed interleukin-6 and nitric oxide production, whereas overproduction of inflammatory mediators enhanced IDO expression and assisted tryptophan degradation. API also inhibited activation of extracellular signal-regulated kinase (Erk) and jun N-terminal kinase (JNK) MAPK, and degradation of IκBα. [Significance ] These results indicate alteration of ACMSD expression under inflammatory conditions. Moreover, API recovers expression of tryptophan metabolic key enzymes, which may be mediated by inhibition of proinflammatory mediator production via inactivation of Erk, JNK MAPK, and NF-κB pathways in LPS-stimulated microglial cells.